The Markers of Body Size and Shape of Bali Cattle and its Crosses with Exotic Bulls - Muh. Rusdin; La Ode Nafiu; Achmad Selamet Aku; La Ode Sahaba (Postgraduate, University of Mataram, 2025)
One of the genetic improvement efforts to improve the performance of Bali cattle offspring production is crossbreeding Bali cattle with exotic bulls. This study aimed to identify markers of body size and shape of Bali cattle and its crosses with exotic bulls using principal component analysis. The materials used in this study were 91 heads of Bali, Simbal, Brahmbal, Limbal, and Pobal cattle, consisting of 34 males and 57 females. The variables observed were body measurements (morphometrics) consisting of shoulder height, body length, chest circumference, chest depth, chest width, hip height, and hip width. Data analysis used Principal Component Analysis in the Minitab Release 19 statistical application. The results showed that Bali, Simbal, Brahmbal, Limbal, and Pobal male cattle had the same body size markers, namely chest circumference. The body shape markers of male cattle are hip height for Bali cattle, chest length for Simbal and Pobal cattle, chest depth for Brahmbal cattle, and hip width for Limbal cattle. The body shape markers in female cattle are body length for Bali, Simbal, Brahmbal, and Pobal cattle, and hip height for Limbal cattle. These body size and shape markers have a strong correlation with the first principal component and the second principal component, so they can be used as selection criteria to improve the production performance of Bali and Bali crossbred cattle.